Isolation and characterization of Pasteurella Multocida from animals and birds - Ambili K (Department of Veterinary Microbiology,College of Veterinary and Animal Sciences, 2010)
A total of 284 samples comprising of tracheal, nasal and pharyngeal swabs, heart blood and tissues like liver, spleen, heart and lungs were processed for isolation of P. multocida. Twenty isolates were obtained from different species of animals and birds, which were characterized as P. multocida by morphological, cultural and biochemical tests. Reference strains of P. multocida P52 and DP1were used for comparison. All the isolates were found to be pathogenic for mice. Based on the variation in fermentation patterns of arabinose, dulcitol, sorbitol, xylose and trehalose the 20 isolates could be grouped into eight biovars. Three biotypes P. multocida subsp gallicida, P. multocida subsp septica and P. multocida subsp. multocida were observed among the twenty isolates. All isolates were uniformly sensitive to norfloxacin, gentamicin, cefotaxime, nitrofurantoin, erythromycin and chloramphenicol. All were resistant to metronidazole and sulphadiazine. A species-specific PCR assay using primer pair KMT1SP6 and KMT1T7 was used to confirm the identity of the isolates. All the isolates obtained were confirmed as serogroup A P. multocida when subjected to multiplex PCR, using PM– specific, Cap A, Cap B, Cap D and Cap F primer pairs. Pasteurella multocida could be detected in only 6 out of 75 clinical samples tested by species specific PCR (PM-PCR). The entire samples tested positive by PM-PCR were confirmed as type-A P. multocida by multiplex PCR. The PCR product (460 bp) of 20 isolates and 5 clinical samples amplified by using primer pairs KMT1SP6 and KMT1T7 when used for reamplification with nested PCR primers, a product of 214 bp size was observed. A high proportion of the clinical samples previously found negative by PM-PCR gave positive results in nested PCR. All the 20 isolates of P. multocida, which were found to be positive by PM-PCR, were subjected to REP-PCR, using the primer pairs REP-1 and REP-2. Pasteurella multocida isolates demonstrated 3 distinct REP profiles, indicating heterogeneity among the isolates. The genomic DNA isolated from all the twenty isolates of P. multocida from different animals and birds were subjected to REA with restriction enzymes Hpa II and Hha I. Four different banding patterns were observed among the 20 isolates of P. multocida when they were subjected to REA with Hpa II, while five REA profiles were obtained with Hha I. In conclusion, PCR assays could be used for the rapid identification and serogrouping of P. multocida from both cultures and clinical samples. The different molecular techniques used in the present study showed genetic heterogeneity among the isolates of P.multocida serogroup A. The results suggested that there was no correlation between the results obtained in REP-PCR and REA. Also among the enzymes used in DNA fingerprinting of P. multocida isolates by REA, Hha I was found to have more discriminatory power. Since only lesser number of samples were used in the current study, a definite conclusion could not be drawn in this basis.